Yiribana : Aboriginal and Torres Strait Islander Gallery - Art Gallery of New South Wales; Neale, Margo (Sydney : The Gallery, 1994)
Brochure developed for the opening of the Yiribana Gallery of Aboriginal and Torres Strait Islander art at the Art Gallery of New South Wales ; provides an overview of Aboriginal art and information on the collection's seven themes ; 'classic' bark paintings and sculptures ; growth and diversity of Aboriginal art over the past half century.
"The word Yiribana means 'this way'. It derives from the Eora language, spoken by the original people of Sydney."
"This brochure ... contains excerpts from the book Yiribana."
Bibliography: p. 2.
Keywords: Art Gallery of New South Wales -- Exhibitions; Art, Aboriginal Australian -- Exhibitions; Art, Torres Strait Islander -- Exhibitions; Art - Sculpture; Torres Strait Islanders (Qld TSI SC54, SC55); Art - Economic aspects - Markets - Market places; Art - Production - Materials / techniques; Art - Painting - Bark; Art - Painting; New South Wales (NSW)